Menuju Perlindungan Sinergis: Diagnosis Kesenjangan Tata Kelola Kolaboratif bagi Pekerja Migran Indonesia di Jawa Tengah - Supriyanto, Hery; Hartawan, Wisnu (Brawijaya University, 2025)
This study explores the gaps and enabling factors in implementing collaborative governance to protect Indonesian Migrant Workers (PMI) at the regional level, using Central Java as a case study. Despite existing policies, protection remains government-dominated, with limited non-governmental involvement. Preventive efforts are lacking because responses tend to be reactive. Through qualitative document analysis, this study examines four dimensions: initial conditions, institutional design, leadership, and collaboration processes. The findings indicate ineffective collaboration due to weak stakeholder engagement. Strengthening partnerships between government and non-governmental actors is essential to enhance migrant worker protection and contribute to regional poverty reduction efforts